Bats and Human Health: Ebola, SARS, Rabies and Beyond - Beltz, Lisa A (Wiley, 2017)
An important resource that reviews the various infectious diseases that affect bats and bat populations Bats and Human Health: Ebola, SARS, Rabies and Beyond covers existing literature on viral, bacterial, protozoan, and fungal infections of bats and how these infections affect bat populations. The book also offers an overview of the potential for zoonotic transmission of infectious diseases from bats to humans or domestic animals. While most prior publications on the subject have dealt only with bat viral infections, this text closely covers a wide range of bat infections, from viral and bacterial infections to protist and fungal infections. Chapters on viral infections cover rabies, filoviruses, henipaviruses, and other RNA viruses, as well as information on bat virome studies. The book then provides information on bacterial infections–including arthropod-borne and other bacteria that affect bats–before moving on to protist infections, including apicomplexans and kinetoplastids, and fungal infections, including white-nose syndrome, histoplasma capsulatum, and other fungi. Comprehensive in scope, yet another key feature of this book is a searchable database that includes bat species, bat family, bat diet, bat location, type and classification of infecting microbes, and categories of microbes. This vital resource also: * Provides a history and comprehensive overview of bat-borne diseases * Incorporates information from the World Health Organization, as well as historical data from the National Libraries of Health and infectious disease journals * Covers a variety of diseases including viral infections, bacterial infections, protist infections, and fungal infections Written for microbiologist, bat researchers, and conservationists, Bats and Human Health provides a comprehensive exploration of the various types of microbes that affect bats and their potential to affect human populations.